GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 14 Oct 2019, 03:41 GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  S97-16

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

Hide Tags

Math Expert V
Joined: 02 Sep 2009
Posts: 58312

Show Tags 00:00

Difficulty:   25% (medium)

Question Stats: 81% (02:06) correct 19% (01:59) wrong based on 21 sessions

HideShow timer Statistics

$$x$$ is replaced by $$1 - x$$ everywhere in the expression $$\frac{1}{x} - \frac{1}{1 - x}$$, with $$x \neq 0$$ and $$x \neq 1$$. If the result is then multiplied by $$x^2 - x$$, the outcome equals

A. $$x + 1$$
B. $$x - 1$$
C. $$1 - x^2$$
D. $$2x - 1$$
E. $$1 - 2x$$

_________________
Math Expert V
Joined: 02 Sep 2009
Posts: 58312

Show Tags

Official Solution:

$$x$$ is replaced by $$1 - x$$ everywhere in the expression $$\frac{1}{x} - \frac{1}{1 - x}$$, with $$x \neq 0$$ and $$x \neq 1$$. If the result is then multiplied by $$x^2 - x$$, the outcome equals

A. $$x + 1$$
B. $$x - 1$$
C. $$1 - x^2$$
D. $$2x - 1$$
E. $$1 - 2x$$

First, carry out the replacement. Literally replace every $$x$$ in the expression with $$1 - x$$, putting parentheses around the $$1 - x$$ in order to preserve proper order of operations:

Original: $$\frac{1}{x} - \frac{1}{1 - x}$$

Replacement:
$$\frac{1}{(1 - x)} - \frac{1}{1 - (1 - x)}$$

Now simplify the second denominator: $$(1 - (1 - x)) = (1 - 1 + x) = x$$

So the replacement expression becomes this:
$$\frac{1}{(1 - x)} - \frac{1}{x}$$

This should make sense. If we replace $$x$$ by $$1 - x$$, then it turns out that we are also replacing $$1 - x$$ by $$x$$ (since $$1 - (1 - x) = x$$). Thus, the denominators of the original expression are simply swapped.

Now we can either combine these fractions first (by finding a common denominator) or go ahead and multiply by $$x^2 - x,$$ as we are instructed to. Let’s take the latter approach.
$$( \frac{1}{1 - x} - \frac{1}{x}) (x^2 - x)$$

Instead of FOILing this product right away, we should factor the expression $$x^2 - x$$ first. If we do so, we will be able to cancel denominators quickly.

$$x^2 - x$$ factors into $$(x - 1)x$$. We can now rewrite the product:
$$( \frac{1}{1 - x} - \frac{1}{x} ) (x - 1)x = \frac{(x - 1)x}{(1 - x)} - \frac{(x - 1)x}{x}$$

The second term, $$\frac{(x - 1)x}{x}$$, becomes just $$x - 1$$ after we cancel the $$x$$'s.

Since $$(x - 1) = -(1 - x)$$, we can rewrite the first term as $$\frac{-(1 - x)x}{(1 - x)}$$ and then cancel the $$(1 - x)$$’s, leaving $$-x$$.

So, the final result is $$-x - (x - 1) = -x - x + 1 = 1 - 2x$$. This is the answer.

Separately, since this is a Variables In Choices problem, we could instead pick a number and calculate a target. Since 0 and 1 are disallowed, let's pick $$x = 2$$. We are told that $$x$$ should be replaced by $$1 - x$$, so we calculate $$1 - x = -1$$ and put in -1 wherever $$x$$ is in the original expression.
$$\frac{1}{x} - \frac{1}{(1 - x)} = \frac{1}{(-1)} - \frac{1}{(1 - (-1))} = -1 - \frac{1}{2} = -\frac{3}{2}$$

Now multiply this number by $$x^2 - x = 2^2 - 2 = 2$$. We get -3 as our target number.

Finally, we plug $$x = 2$$ into the answer choices and look for -3:

(A) $$x + 1 = 2 + 1 = 3$$

(B) $$x - 1 = 2 - 1 = 1$$

(C) $$1 - x^2 = 1 - 2^2 = -3$$

(D) $$2x - 1 = 2(2) - 1 = 3$$

(E) $$1 - 2x = 1 - 2(2) = -3$$

We can eliminate choices A, B, and D, but to choose between C and E, we would need to pick another number.

_________________
Intern  B
Joined: 30 Jan 2018
Posts: 2

Show Tags

Found an easier way to solve this problem.
Assume (1-x) to be equivalent to a variable r.
Now the solution becomes 1/r - 1/x * x*-r
=> (x-r)/xr * (-rx) (cancel the numerator and denominator to get -1(x-r) = r-x
=> Now substitute r = 1-x
=> 1-x-x = 1-2x
Solution = E.
Intern  Joined: 17 Mar 2019
Posts: 3

Show Tags

I think this the explanation isn't clear enough, please elaborate. the last part of the solution is a little unclear. Can it be explained in a little more algebraic depth?

x2−xx2−x factors into (x−1)x(x−1)x. We can now rewrite the product:

(11−x−1x)(x−1)x=(x−1)x(1−x)−(x−1)xx(11−x−1x)(x−1)x=(x−1)x(1−x)−(x−1)xx$The second term, (x−1)xx(x−1)xx, becomes just x−1x−1 after we cancel the xx's. Since (x−1)=−(1−x)(x−1)=−(1−x), we can rewrite the first term as −(1−x)x(1−x)−(1−x)x(1−x) and then cancel the (1−x)(1−x)’s, leaving −x−x. So, the final result is −x−(x−1)=−x−x+1=1−2x−x−(x−1)=−x−x+1=1−2x. This is the answer Math Expert V Joined: 02 Sep 2009 Posts: 58312 Re: S97-16 [#permalink] Show Tags asfandkhan wrote: I think this the explanation isn't clear enough, please elaborate. the last part of the solution is a little unclear. Can it be explained in a little more algebraic depth? x2−xx2−x factors into (x−1)x(x−1)x. We can now rewrite the product: (11−x−1x)(x−1)x=(x−1)x(1−x)−(x−1)xx(11−x−1x)(x−1)x=(x−1)x(1−x)−(x−1)xx$
The second term, (x−1)xx(x−1)xx, becomes just x−1x−1 after we cancel the xx's.

Since (x−1)=−(1−x)(x−1)=−(1−x), we can rewrite the first term as −(1−x)x(1−x)−(1−x)x(1−x) and then cancel the (1−x)(1−x)’s, leaving −x−x.

So, the final result is −x−(x−1)=−x−x+1=1−2x−x−(x−1)=−x−x+1=1−2x. This is the answer

You can find more solutions here: https://gmatclub.com/forum/x-is-replace ... 88681.html
_________________ Re: S97-16   [#permalink] 12 May 2019, 21:17
Display posts from previous: Sort by

S97-16

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

Moderators: chetan2u, Bunuel

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne  